Analyzing life-cycle water footprint for advanced bio-liquid fuel: Crop residues and non-grain biofuels in China. (15th April 2021) - Huang, Yuting; Chen, Chunxiang; Huang, Haozhong
Abstract: Increasing the production of biofuels in some provinces of China may be affected by local water resources (WR). This study analyzed the life-cycle water footprint (WF) of second-generation and non-grain fuels in different natural and technical conditions in different provinces of China. The analysis was doing using the CROPWAT software model, comparing conversion technologies, a sensitivity analysis, uncertainty analysis, and a pressure analysis of local WR. The impact of biofuel on the WF and local water load in Northeast, Southwest, Northwest, Central, and South China were analyzed. Results show that the bio-ethanol of Bagasse and Cassava in Guangxi, Sorghum stalk in Jilin, and Paddy Rice straw and Corn cobs in Heilongjiang are the most favorable feedstocks for producing biofuel, with WFs ranging from to 152–967 m 3 /t. The proportions of grey WF to life-cycle WF for Sorghum straw (61.89%), Corn cob bio-ethanol (60.17%), and Rapeseed biodiesel (85.20%) in China should be reduced compared with the global average WF (less than 50%). The local WR load of Wheat straw in Henan was the highest ( K  = 1.13) and the local WR load of Bagasse in Guangxi was lowest ( K  = 0.06). Increasing the output, reducing the value fraction of the crop residue, and reducing chemical fertilizer consumption have the best effect on reducing WF. Biofuel development policies, including adopting well-designed management practices, controlling fertilizer use as much as possible, carrying out nearby bioenergy strategies, and implementing a local multi-cooperation model are proposed. These results can guide provincial decision-making to expand biofuel commercialization in China. Graphical abstract: Image 1 Highlights: Life-cycle water footprint (WF) of bio-liquid fuels in China was assessed. The uncertainty of life-cycle WF was determined. The bioethanol of Bagasse, Rice straw, Sorghum stalk and Corn cob had more potential. Local water loads of biofuels were quantified and China' biofuel had high grey water. Water-saving biofuels need concerted management and regional cooperation models.